Impacto das políticas de transferência de renda nos fluxos migratórios do Brasil : o programa bolsa família - Meza Quezada, Santiago Josué (2014)
This research aims to analyze the impact that has the Cash Transfer Program with Conditionalities, popularly known as Bolsa Família Program in emigration flows of microregions of Brazil. The Bolsa Família program is the most important social policy with the broadest coverage that the Brazilian government has implemented lately. This program consists in a monthly cash transfer to the most vulnerable sectors of the population. Quantifying the effect of the program in emigration is performed using the average treatment effect on the beneficiaries in the condition of being a migrant or not. Two algorithms are used in the methodology of propensity score matching (PSM) using data from the 2010 Population Census. The results show that there is a negative and significant impact of the Bolsa Família Program in emigration flows.